Analysis of Polymorphisms in 59 Potential Candidate Genes for Association With Human Longevity. (30th December 2017) - Donlon, Timothy A; Morris, Brian J; Chen, Randi; Masaki, Kamal H; Allsopp, Richard C; Willcox, D Craig; Tiirikainen, Maarit; Willcox, Bradley J
Abstract: Longevity is a polygenic trait in which genetic predisposition is particularly important. We hypothesized that among genes differentially expressed in response to caloric restriction, several may be candidate longevity genes. We tested 459 single-nucleotide polymorphisms (SNPs) in 47 genes differentially expressed in calorically restricted mice and 12 other genes for association with longevity. Subjects were American men of Japanese ancestry, 440 aged ≥95 years and 374 with an average life span. Based on a dominant model of inheritance, an association with longevity at the p < .05 level was seen for SNPs in 13 of the genes. Testing by all possible models increased the number of genes to 18. After correction for multiple testing, four genes retained significance, namely, MAP3K5 ( p = .00004), SIRT7 ( p = .00004), SIRT5 ( p = .0007), and PIK3R1 ( p = .01). In a dominant model, association with longevity was seen for multiple adjacent SNPs within two of these genes ( MAP3K5 and PIK3R1 ), as well as in FLT1, consistent with linkage disequilibrium with a causative variant in the vicinity of each respective SNP set. MAP3K5 and FLT1 haplotypes were associated with longevity. In conclusion, the present study implicates variation in MAP3K5, FLT1, PIK3R1, SIRT7, and SIRT5 in human longevity.